Pengaruh Pengetahuan Kewirausahaan Dan Efikasi Diri Terhadap Minat Berwirausaha Dengan Motivasi Berwirauaha Sebagai Variabel Intervening (Studi Pada Mahasiswa Manajemen Angkatan 2019 Universitas Muhammadiyah Metro) - Febiyanto; Ardiansyah Japlani; Fariz Rubihatlan (Jurnal Manajemen DIVERSIFIKASI, 2024)
Based on the latest data from the Central Statistics Agency (BPS) shows that as of February 2022, Indonesia's unemployment rate was recorded at 5.83 percent of the total working age population of 208.54 million people. Which astonishing, of the 5.83 percent, almost 14% were residents diploma and bachelor degree (S1) graduates. Based on these data state Indonesia it self still really needs new entrepreneurs, because It is hoped that with the increasing number of entrepreneurs in Indonesia, create new jobs, reduce unemployment and also can help improve the economy of the surrounding community as well country. This research has a goal, namely to find out whether Entrepreneurial knowledge influences the interest in entrepreneurship. For determine whether self-efficacy affects the interest in entrepreneurship. For determine whether entrepreneurial knowledge affects motivation entrepreneurship. To find out whether self-efficacy has an effect on entrepreneurial motivation. To find out whether entrepreneurial knowledge and self-efficacy influences the interest in entrepreneurship with motivation entrepreneurship as an intervening variable. The sample of this research is Class of 2019 Management Student at Muhammadiyah Metro University as many as 102 students. Data collection using a questionnaire, and data analysis using validity test, reliability test, normality test, test linearity, Heteroscedasticity Test, Multicollinearity Test, linear regression analysis multiple, t test, f test, r determination test, and Regression Analysis of Mediation Variables With the Causal Step Method using the program (SPSS). Results research shows that there is a positive and significant influence Entrepreneurship Knowledge and Self-Efficacy on Entrepreneurial Interests, there is a positive and significant influence on Entrepreneurship Knowledge and Efficacy Self on Entrepreneurial Motivation, and there is a positive and significant influence Entrepreneurship Knowledge and Self-Efficacy on Entrepreneurial Interests With Entrepreneurial Motivation as an Intervening Variable.